Assessing the association between subjective evaluation of space qualities and physiological responses through cinematic environments’ emotion-eliciting stimuli - Sakhaei, Hamidreza; Gu, Ning; Looha, Mehdi Azizmohammad (Frontiers in Psychology, 2023)
Objectives: Human perception of the built environment affects emotional and physiological states. This research focused on the association between evaluating a space’s visual qualities and physiological responses by mediating film contents to indicate the association between physiological indicators and assessing the quality of space in the presence of environmental stimuli. Method: Data collection was conducted using a psychological questionnaire and physiological indicators of HR, BP, SRL, and BT during the film screening. The ANOVA was conducted to compare different variables in the three films alongside linear regression to analyze the impact of variables on space quality. Spearman correlation coefficient analyses were performed to find the association between variables. Results: The descriptive statistics showed significant changes in psychological and physiological variables in films. Associations between the NAQ factor and physiological changes in HR, SBP, and DBP factors were significant. The results derived from the simple and multiple linear regressions depicted the significant impact of physiological factors on HR and BP on perceiving the quality of space. Conclusion: It was concluded that physiological changes caused by emotional arousal could be strongly associated with psychological assessments. Stimuli-affected video contents illustrating architectural spaces could efficiently extract the impact of physiological states and human cognitive responses to the space quality. Physiological characteristics related to the space appraisal could help realize the human-environment interaction in a multi-layered approach to the built environment and spatial cognition.